2008
DOI: 10.2165/00148581-200810040-00005
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Pharmacokinetics of Lansoprazole in Neonates and Infants

Abstract: The pharmacokinetics of lansoprazole in pediatric patients are age dependent, with those aged 10 weeks-1 year. Thus, pediatric patients aged 10 weeks to achieve similar plasma exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 24 publications
0
4
0
2
Order By: Relevance
“…A consistent finding from pharmacokinetic studies of PPIs in neonates and infants is a significantly reduced plasma drug clearance in the first month of life, which is associated with a reciprocal increase in systemic exposure (as measured by dose‐normalized area under the plasma concentration vs. time curve (AUC)) 14 , 15 , 16 . Also, as reflected by composite data for apparent pantoprazole clearance over the first 5 months of postnatal life (), there is considerable variability in the pharmacokinetics of the drug produced by development and, potentially, CYP2C19 polymorphism.…”
Section: The Proton Pump Inhibitorsmentioning
confidence: 87%
“…A consistent finding from pharmacokinetic studies of PPIs in neonates and infants is a significantly reduced plasma drug clearance in the first month of life, which is associated with a reciprocal increase in systemic exposure (as measured by dose‐normalized area under the plasma concentration vs. time curve (AUC)) 14 , 15 , 16 . Also, as reflected by composite data for apparent pantoprazole clearance over the first 5 months of postnatal life (), there is considerable variability in the pharmacokinetics of the drug produced by development and, potentially, CYP2C19 polymorphism.…”
Section: The Proton Pump Inhibitorsmentioning
confidence: 87%
“…The increased metabolic capacity, instead, is present in children (1-6 years), so an increased dose of PPIs according to weight should be considered [26]. Moreover, several studies have shown that preterm infants and term neonates present an immaturity of drugmetabolizing enzyme pathways (CYP2C19, CYP3A4) [27,28], and this could explain the higher systemic exposure to PPIs in this population than in older children [29][30][31].…”
Section: Pharmacokinetics Of Ppis In Pediatricsmentioning
confidence: 99%
“…B. 0,3 mg/kg Körperge-wicht und Tag), um eine Überdosierung zu verhindern [23]. Eine Verschreibung von PPI sollte bei Säuglingen deswegen besonders restriktiv und nicht nur auf Basis von Symptomen gehandhabt werden.…”
Section: E Bisher Ist Kein Protonenpumpeninhibitor Für Das Alter Unteunclassified